Is birdsong music? Evaluating harmonic intervals in songs of a Neotropical songbird - Araya Salas, Marcelo (2012)
Signals in animal communication are commonly judged as aesthetically appealing by human standards. This is particularly common for birdsong, often equated to musical compositions. No formal test, however, has analysed the harmonic properties of bird vocalizations. Musical intervals are based on the same physical characteristics of sound that underlie animal vocal signals. Thus, animals may use these intervals as rules to organize their vocalizations in a similar way as music. I tested a prediction derived from this hypothesis, that frequency ratios of adjacent notes in birdsong are closer to harmonic intervals than expected by chance. I determined to what degree the intervals created by adjacent notes of the song of nightingale wrens, Microcerculus philomela, conform to harmonic intervals. I analysed songs from 81 birds across the entire distribution range of the species, comparing the intervals formed by adjacent notes to three musical scales: chromatic, major diatonic and major pentatonic. Comparisons were made based on null model distributions. From 243 comparisons, only six (w2%) were significantly close to harmonic intervals, suggesting no consistent use of harmonic intervals. The frequency of the notes is the most varying song parameter in this species. If the frequencies are not determined by harmonic intervals in this species, it seems less likely that it happens in other birds with more complex song elements. Documented musical properties in birds might be caused by cultural biases of the listener or misunderstanding of the physics of musical compositions.